ETHNIC PROCESSES IN KHIVA AND ITS NEIGHBORING COUNTRIES IN "SHAJARAII TURKISH" BY ABULGAZI BAHODIRKHAN - N.Sh. Hamraeva (Current Research Journal of History, 2021)
The article provides a brief overview of the socio-political, economic and cultural life of Khiva and neighboring regions in the Middle Ages, coverage of ethnic processes in the work of Abulgazi Bakhodirkhan "Shajaray Turkish".